Sympathetic Hyperactivity and Sleep Disorders in Individuals With Type 2 Diabetes - López-Cano, Carolina; Gutiérrez-Carrasquilla, Liliana; Sánchez, Enric; González, Jessica; Yeramian, Andree; Martí, Raquel; Hernández, Marta; Cao, Gonzalo; Ribelles, Mercè; Gómez, Xavier; Barril, Silvia; Barbé, Ferran; et al. (Frontiers in Endocrinology, 2019)
Introduction. Many studies on the impact of type 2 diabetes mellitus (T2DM) on sleep breathing have shown a higher prevalence and severity of sleep apnea-hypopnea syndrome (SAHS) in those with T2DM. Moreover, an increased activity of the sympathetic nervous system has been described in both pathologies. This cross-sectional study aimed to assess sympathetic activity in patients with T2DM, and to investigate the relationship between sympathetic activity and polysomnographic parameters. Materials and methods. Thirty-six patients with T2DM without known clinical macrovascular nor pulmonary disease and eleven controls underwent respiratory polygraphy, and their cardiac variability and 24-hour urine total metanephrines were measured. Results: SAHS was highly prevalent with a mean apnea-hypopnea index (AHI) in the range of moderate SAHS. In patients with T2DM, the nocturnal concentration of total metanephrines in urine were higher than diurnal levels [247.0 (120.0-1375-0) vs. 210.0 (92.0-670.0), p=0.039]. The nocturnal total metanephrine concentration was positively and significantly associated with the percentage of sleeping time spent with oxygen saturation <90%(CT90). In the entire population and in subjects with T2DM, the multivariate regression analysis showed a direct interaction between the nocturnal concentration of urine metanephrines and the CT90. Conclusion: These findings suggest that the increase in sympathetic activity previously described in patients with T2DM could be mediated through nocturnal breathing disturbances. The diagnosis and treatment of SAHS may influence sympathetic activity disorders and may contribute to an improvement in T2DM and cardiovascular risk.